2002
DOI: 10.1002/gea.10003
|View full text |Cite
|
Sign up to set email alerts
|

The good earthworm: How natural processes preserve upland Archaic archaeological sites of western Illinois, U.S.A.

Abstract: In western Illinois, many soil profiles developed into upland loess deposits (Peoria Silt) contain Archaic period artifacts greater than 3500 yr B.P. in stone zones below plow level. For artifacts in prairie and prairie-forest transition soils (not forest soils), depth distribution curves suggest they were buried in biomantles by small soil fauna. Artifacts of sizes archaeologists routinely collect generally move down while retaining fine-scale horizontal integrity. The process results in stratigraphic separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 71 publications
2
23
0
1
Order By: Relevance
“…One may wonder whether this is an accurate depiction of reality or if it reflects undue optimism. Van Nest (2002) seems to share this optimism, at least with respect to earthworms, and emphasized that these animals may enhance the stratigraphic separation of occupations deposited at different times.…”
Section: How Does Faunalturbation Affect the Integrity Of Archaeologimentioning
confidence: 90%
See 1 more Smart Citation
“…One may wonder whether this is an accurate depiction of reality or if it reflects undue optimism. Van Nest (2002) seems to share this optimism, at least with respect to earthworms, and emphasized that these animals may enhance the stratigraphic separation of occupations deposited at different times.…”
Section: How Does Faunalturbation Affect the Integrity Of Archaeologimentioning
confidence: 90%
“…This density is moderate compared to sites located farther south or in Europe (Stein, 1983;Van Nest, 2002). At Pointe-du-Buisson, earthworms and other animals are very rare in the compact clays found below the topsoil.…”
Section: Agents Of Faunalturbation At Pointe-du-buissonmentioning
confidence: 91%
“…For example, Van Nest (2002) reports that Archaic-aged FCR occurred in abundance some 35 cm below surface at a silty sediment case study site in Illinois, but intact features more than 2,500 years old were apparently lacking altogether. She attributed these patterns to biomantle and stone-zone formation.…”
Section: Fire-cracked Rock Features On Sandy Landformsmentioning
confidence: 95%
“…Implementation of such studies, however, is a scientific challenge in that upland settings tend to undergo net erosion and, other things being equal, sites there are likely to be poorly preserved compared to those in alluvial bottomlands. A substantial body of geoarchaeological data has been compiled and synthesized about impacts to archaeological sites from pedoturbation, but considerable epistemological debate remains about site integrity issues at upland sites (e.g., Wood and Johnson, 1978;Burtchard, 1987;Schiffer, 1987;Johnson and Watson-Stegner, 1990;Bocek, 1992;Leigh, 2001;Balek, 2002;Frederick et al, 2002;Johnson, 2002;Peacock and Fant, 2002;Van Nest, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the topic by many authors has shown that more often than expected, archaeological materials have the tendency of not staying where they were deposited (e.g., Bordes, 1972;Cahen and Moeyersons, 1977;Siiriä inen, 1977;Moeyersons, 1978;Rolfsen, 1980;Villa, 1982aVilla, , 1982b. Among the many variables responsible for displacement of artifacts is the action of burrowing animals such as ants, termites, earthworms, and rodents (Stein, 1983;Bocek, 1986;Johnson, 1990Johnson, , 1993Johnson, , 2002Pierce, 1992;Araujo, 1995;Balek, 2002;Van Nest, 2002). There is, however, one animal that despite its regional VOL.…”
Section: Introductionmentioning
confidence: 99%